An Optimum Reverberation Time for Mosques in Bangladesh - Imam, Sheikh Muhammad Najmul; Ahmed, Nizamuddin; Takahashi, Daiji (Bangladesh Journal of Scientific and Industrial Research, 2009)
For a mosque in Bangladesh, the acoustical requirements in terms of intelligibility and liveliness are dissimilar for the types of sounds - recitation from the Holy Koran and speech on religious subjects. To attain an overall satisfactory acoustical performance, it is significant to find an optimum Reverberation Time (RT), which is one of the important factors affecting intelligibility and liveliness. Experiment is conducted to find the effect of RT by making it a variable, while keeping other factors as non-variable and fulfilling ideal conditions for maximum intelligibility. Preferences are judged on pairs of sound clips of recitation and speech, for both intelligibility and liveliness, on a 5-point scale and findings are analysed thorough the statistical method of paired comparison. Considering preferences of all aspects the optimum RT is proposed as 0.9 s for an overall balanced acoustical performance for both recitation and speech for a mosque in Bangladesh. Keywords: Intelligibility, Liveliness, Mosque, Recitation, Reverberation time, Speech. DOI: 10.3329/bjsir.v44i2.3667 Bangladesh J. Sci. Ind. Res. 44(2), 163-170, 2009